Issues behind the Utilization of Community Mental Health Services by Ethnic Minorities in Hong Kong. Issue 7 (3rd October 2022) - Kwan, Chi Kin; Lo, Kai Chung
ABSTRACT: This study collected data on the utilization rates of community mental health services among ethnic minorities and explained the results from the frontline social workers' perspective. Information about users' ethnicity was collected from 11 community mental health service providers from 2015 to 2018. This was followed by two sessions of focus groups conducted with 10 frontline social workers from six community mental health centers in Hong Kong. A hybrid analysis model was employed to analyze the qualitative data. The average utilization rates of community mental health services by ethnic minorities were 0.49%, 0.58%, and 0.68% in the years 2015–16, 2016–17, and 2017–18, respectively, showing that ethnic minorities who comprised 8% of the population were significantly underrepresented. It is worth noting that supply-side and demand-side factors are interrelated, suggesting the low utilization rate may be overcome by implementing a proactive social work service strategy.